Rice OsERF71-mediated root modification affects shoot drought tolerance - Lee, Dong-Keun (Plant Signal Behav, 2016)
Drought is the most serious problem that impedes crop development and productivity worldwide. Although several studies have documented the root architecture adaption for drought tolerance, little is known about the underlying molecular mechanisms. Our latest study demonstrated that overexpression of the OsERF71 in rice roots under drought conditions modifies root structure including larger aerenchyma and radial root growth, and thereby, protects the rice plants from drought stresses. The OsERF71-mediated root modifications are caused by combinatory overexpression of general stress-inducible, cell wall-associated and lignin biosynthesis genes that contribute to drought tolerance. Here we addressed that the OsERF71-mediated root modifications alter physiological capacity in shoots without evidence of developmental changes for drought tolerance. Thus, the OsERF71-mediated root modifications provide novel molecular insights into drought tolerance mechanisms.